2007
DOI: 10.1121/1.2535507
|View full text |Cite
|
Sign up to set email alerts
|

Noise within the social context: Annoyance reduction through fair procedures

Abstract: The social context of noise exposure is a codeterminant of noise annoyance. The present study shows that fairness of the exposure procedure ͑sound management͒ can be used as an instrument to reduce noise annoyance. In a laboratory experiment ͑N = 117͒ participants are exposed to aircraft sound of different sound pressure level ͑SPL: 50 vs 70 dB A͒-which is experienced as noisewhile they work on a reading task. The exposure procedure ͑fair versus neutral͒ is modeled in line with findings from social justice the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 42 publications
2
39
0
1
Order By: Relevance
“…In other words: Can a procedurally unfair interaction with the operators of the sound source cause excess noise annoyance? The present experiment largely replicates the earlier experiment by Maris et al ͑2007͒. Participants go through a noise management procedure before they are to perform a reading task while being exposed to annoying sound ͑played at 50 or 70 dB A͒.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…In other words: Can a procedurally unfair interaction with the operators of the sound source cause excess noise annoyance? The present experiment largely replicates the earlier experiment by Maris et al ͑2007͒. Participants go through a noise management procedure before they are to perform a reading task while being exposed to annoying sound ͑played at 50 or 70 dB A͒.…”
Section: Introductionmentioning
confidence: 86%
“…1; for a more detailed description of the experimental model see Maris et al ͑2007͔͒. In the model, noise annoyance is represented as an expression of psychological stress, arising when the perceived level of disturbance due to the sound outgrows the perceived level of control over the sound ͑"internal processes"͒. People are expected to pay attention to the sound and to the sound management procedure; therefore both are included on the stimulus side of the model ͑"external processes"͒.…”
Section: Introductionmentioning
confidence: 99%
“…The notations also indicated that the perception of the annoyance depended on the possibility to influence or control the annoying sound. It was previously shown that the possibility to control a sound source was of great importance for the degree of annoyance (Maris et al, 2007). Consequently, a limitation in the ability to influence the surroundings can affect the ability to cope or endure annoying sounds.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of trust has been one of the elements that has undermined the relationship between Gavà Mar residents and the other the stakeholders. Maris et al (2007Maris et al ( , p. 2001 have shown that ''if the exposed has little control over the source, or little trust in the source, the perceived coping resources will be reduced and psychological stress will arise". This also holds true for the case of Barcelona airport.…”
Section: Discussionmentioning
confidence: 98%